The antimicrobial peptide, human β-defensin-1, potentiates in vitro osteoclastogenesis via activation of the p44/42 mitogen-activated protein kinases - Anupong Makeudom (2018)
© 2017 Elsevier Inc. Previous studies have demonstrated increased expression and raised levels of human β-defensin (hBD)-1 in gingival tissue and crevicular fluid of patients with chronic periodontitis and peri-implantitis, oral bone-resorbing diseases caused by enhanced osteoclastogenesis. Therefore, we aimed to investigate the effect of hBD-1 on osteoclast formation and function and to elucidate the involved signaling pathway in vitro. Human peripheral blood mononuclear cells (PBMCs) were first incubated with various doses of hBD-1 and cell viability was assayed by MTT. PBMCs were treated with macrophage-colony stimulating factor and receptor activator of nuclear factor kappa-B ligand (RANKL) in the presence or absence of non-toxic doses of hBD-1. In vitro osteoclastogenesis was analyzed by tartrate-resistant acid phosphatase (TRAP) staining, osteoclast-specific gene expression, and a resorption pit assay. Involvement of mitogen-activated protein kinases (MAPKs) was studied by immunoblotting and specific MAPK inhibitors. HBD-1 potentiated induction of in vitro osteoclastogenesis by RANKL, as shown by significantly increased number of TRAP-positive multinuclear cells and resorption areas on the dentin slices, and further up-regulated expressions of osteoclast-specific genes compared to those by RANKL treatment (p < 0.05). However, hBD-1 treatment without RANKL failed to induce formation of osteoclast-like cells. A significant and further increase in transient phosphorylation of the p44/42 MAPKs was demonstrated by hBD-1 co-treatment (p < 0.05), consistent with the inhibitory effect by pretreatment with U0126 or PD98059 on hBD-1-enhanced osteoclastogenesis. Collectively, hBD-1 potentiates the induction of in vitro osteoclastogenesis by RANKL via enhanced phosphorylation of the p44/42 MAPKs.